Detection and Classification of Genetically Transfered Idiopathic Partial Epilepsy to Child:a Four Rule ANFIS based SWT-EBFO Approach - Mohanta, Debasis; Mahapatra, Sakuntala; Kumar Nayak, Santanu (International Journal of Engineering and Technology, 2018)
Background:-Hereditary qualities have an influence in numerous sorts of epilepsy. In the event that a parent has idiopathic epilepsy, there is around 5% to 8% chance that the youngster upto 8 years will likewise have epilepsy called as idiopathic partial epilepsy (IPE).Methods:-This exploration work breaks down the epilepsy issue exchange hereditarily by coordinating the best properties of Enhanced Bacterial Foraging Optimization (EBFO) and Least-mean-square (LMS) algorithm with four rule Adaptive Neuro-fuzzy Inference System (ANFIS) Network. Stockwell Transform (SWT) strategy searched for the extraction of decomposed signal. In this work, quantitative tests and statistical tests are performed by utilizing SWT-ANFIS-EBFO and SWT-ANFIS-LMS strategies.Results:-Our proposed statistical results(Accuracy (98.30%), sensitivity (98.23%), specificity (99.53%)Â Â and Matthewâ€™s correlation coefficient (97.08%),G-mean (98.88%) and average detection ratio (98.93%)) are calculated withthe network SWT-ANFIS-LMS. Proposed statistical results (accuracy (99.49%), sensitivity (98.78%), specificity (98.56%), and Matthewâ€™s correlation coefficient (97.907%), G-mean (99.172) and average detection ratio (99.174%)) are calculated SWT-ANFIS-EBFO beats. The calculated quantitative test results for network SWT-ANFIS-LMS are (SNR 18.42Â±0.18, RE 0.11Â±0.02, CC 61Â±0.012, MFRE 0.41Â±0.02) and for network SWT-ANFIS-MFRE are (SNR 18.42Â±0.18, RE 0.11Â±0.02, CC 61Â±0.012, MFRE 0.41Â±0.02).Conclusion:-In this paper we endeavor to investigate the best capability of SWT based ANFISnetwork trained with EBFO and LMS algorithms for classification of IPE EEG signals.Calculated statisticaland quantative test results of the proposed method outperforms as compared to existing methods. It will end up being a significant trial device in clinical application and advantageous application towards IPE influenced patients.Â